The female triathlete - Mountjoy, M.; Thomas, A.; Levesque, J. (Triathlon Medicine, 2019)
Participation in triathlon from the recreational to the elite level can provide significant health benefits for female athletes. Regular training in the three triathlon components of swimming, cycling and running can result in the reduction of the risk of developing non-communicable diseases such as hypertension, diabetes mellitus and cardiovascular disease. Other health benefits of triathlon participation include an improvement in bone mineral density, muscular strength, cardiovascular fitness, mental health and well-being. There are however, potential health risks of sport participation in triathlon that are unique to the female athlete. This chapter provides an overview of the following health issues for female triathletes: training, injury prevention, relative energy deficiency in sport (RED-S), nutrition, gynecological issues, pelvic floor dysfunction, mental health, non-accidental violence and doping. The objectives of this chapter are (1) to increase knowledge of relevant topics related to healthy female athlete participation in triathlon, (2) to encourage the adoption of healthy female triathlete sport practices by athletes, coaches and other members of the athlete entourage, and (3) to promote safe participation for female athletes in triathlon. Through the implementation of the prevention and treatment practices outlined in this chapter, female athletes can enjoy the many health benefits of triathlon.